Impact of treatment with saxagliptin on glycaemic stability and β‐cell function in the SAVOR‐TIMI 53 study. Issue 5 (25th February 2015) - Leibowitz, G.; Cahn, A.; Bhatt, D. L.; Hirshberg, B.; Mosenzon, O.; Wei, C.; Jermendy, G.; Sheu, W. H.‐H.; Sendon, J. L.; Im, K.; Braunwald, E.; Scirica, B. M.; et al.
<x xml:space="preserve">Abstract</x> Aims To study the effects of saxagliptin, a dipeptidyl peptidase‐4 inhibitor, on glycaemic stability and β‐cell function in the SAVOR‐TIMI 53 trial. Methods We randomized 16 492 patients with type 2 diabetes (T2D) to saxagliptin or placebo, added to current antidiabetic medications, and followed them for a median of 2.1 years. Glycaemic instability was defined by: (i) a glycated haemoglobin (HbA1c) increase of ≥0.5% post‐randomization; (ii) the initiation of new antidiabetic medications for ≥3 months; or (iii) an increase in dose of oral antidiabetic medication or ≥25% increase in insulin dose for ≥3 months. β‐cell function was assessed according to fasting homeostatic model 2 assessment of β‐cell function (HOMA‐2β) values at baseline and at year 2 in patients not treated with insulin. Results Compared with placebo, participants treated with saxagliptin had a reduction in the development of glycaemic instability (hazard ratio 0.71; 95% confidence interval 0.68–0.74; p < 0.0001). In participants treated with saxagliptin compared with placebo, the occurrence of an HbA1c increase of ≥0.5% was reduced by 35.2%; initiation of insulin was decreased by 31.7% and the increases in doses of an oral antidiabetic drug or insulin were reduced by 19.5 and 23.5%, respectively (all p < 0.0001). At 2 years, HOMA‐2β values decreased by 4.9% in participants treated with placebo, compared with an increase of 1.1% in those treated with saxagliptin (p < 0.0001). Conclusions Saxagliptin improved glycaemia and prevented the reduction in HOMA‐2β values. Saxagliptin may reduce the usual decline in β‐cell function in T2D, thereby slowing diabetes progression.